Relationships between spiritual health and perceived stress with breastfeeding adequacy in mothers with infants aged 1-6 months - Leila Rasaei; Tahmine Dadkhah Tehrani; Zeinab Heidari (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Previous studies have shown that psycho-spiritual state of mothers may have significant effects on their breastfeeding. The most common cause of nonexclusive breastfeeding is inadequate breastfeeding; therefore, this study examined the relationship between spiritual health and perceived stress with breastfeeding adequacy in mothers with infants aged 1-6 months. MATERIALS AND METHODS: This cross-sectional, descriptive, correlational study was performed on 186 mothers with infants aged 1-6 months, who referred to the health centers in Dorud city of Lorestan province, Iran, in 2021, which were selected based on cluster sampling. Data were collected through four questionnaires including demographic-fertility, spiritual health, perceived stress, and breastfeeding adequacy. Data was analyzed by Statistical Package for the Social Sciences (SPSS) software version 22 using descriptive and analytical statistics. RESULTS: The mean ± standard deviation (SD) values of spiritual health, perceived stress, and breastfeeding adequacy were 99.59 ± 12.96, 23.8 ± 72.19, and 55.67 ± 7.67, respectively. There was a significant positive relationship between spiritual health and breastfeeding adequacy (P < 0.001, r = 0.268). In addition, there was a significant negative relationship between perceived stress and breastfeeding adequacy (P = 0.002, r = −0.231). CONCLUSION: Breastfeeding adequacy has a significant positive relationship with spiritual health and a significant negative relationship with perceived stress. Since infants are one of the most vulnerable groups and breastfeeding is the best way to support their health and reduce infant mortality rates, breastfeeding adequacy can be improved by reducing stress and promoting spiritual health.